MOTIVASI, KEPUASAN KERJA DAN PRODUKTIVITAS PENYULUH PERTANIAN LAPANGAN: KASUS KABUPATEN SUKABUMI - Aida Vitayala S. Hubeis (Jurnal Penyuluhan, 2007)
The objective of the study was to find out the motivation, job satisfaction and job productivity of Agriculture Extension Workers (AEW). Respondent of the study was 36 AEW at Sukabumi district, West Java. The results of study have shown that most extension agents are male, relatively old, married and having more than three children. Most of them have had diploma program, participated in several trainings, 20 years of working experience, and belonging to third rank employee. Internal factors of AEW (achievement, recognition, job and responsibility are the internal factors performed significance factors. The motivation of agriculture extension agents has influenced by intrinsic and extrinsic factors; Job satisfaction influenced by psychology, and social, while physical and financial factors have no influence; Job productivity influenced by internal (achievement, recognition, job, responsibility) and external factors (FEW status, interpersonal relation) education background and capacity building, skill, technology, working environment, and discipline. All internal factors, achievement-recognition-work-responsibility has siginificance influence to extension workers productive works.